Cardiovascular care of patients with stroke and high risk of stroke: The need for interdisciplinary action: A consensus report from the European Society of Cardiology Cardiovascular Round Table. (29th August 2020) - Doehner, Wolfram; Mazighi, Mikael; Hofmann, Bernd M; Lautsch, Dominik; Hindricks, Gerhard; Bohula, Erin A; Byrne, Robert A; Camm, A John; Casadei, Barbara; Caso, Valeria; Cognard, Christophe; Diener, Hans-Christoph; et al.
Abstract: Comprehensive stroke care is an interdisciplinary challenge. Close collaboration of cardiologists and stroke physicians is critical to ensure optimum utilisation of short- and long-term care and preventive measures in patients with stroke. Risk factor management is an important strategy that requires cardiologic involvement for primary and secondary stroke prevention. Treatment of stroke generally is led by stroke physicians, yet cardiologists need to be integrated care providers in stroke units to address all cardiovascular aspects of acute stroke care, including arrhythmia management, blood pressure control, elevated levels of cardiac troponins, valvular disease/endocarditis, and the general management of cardiovascular comorbidities. Despite substantial progress in stroke research and clinical care has been achieved, relevant gaps in clinical evidence remain and cause uncertainties in best practice for treatment and prevention of stroke. The Cardiovascular Round Table of the European Society of Cardiology together with the European Society of Cardiology Council on Stroke in cooperation with the European Stroke Organisation and partners from related scientific societies, regulatory authorities and industry conveyed a two-day workshop to discuss current and emerging concepts and apparent gaps in stroke care, including risk factor management, acute diagnostics, treatments and complications, and operational/logistic issues for health care systems and integrated networks. Joint initiatives of cardiologists and stroke physicians are needed in research and clinical care to target unresolved interdisciplinary problems and to promote the best possible outcomes for patients with stroke.